Answer:
<u>1.2</u> is the answer.
Step-by-step explanation:
12/2=6
6/5=1.3
Have a nice day!
Answer:
$48
Step-by-step explanation:
Answer:
(4,1)
Step-by-step explanation:
let J(6,6) be x1, y1
let K(2,-4) be x2, y2
midpoint = (x1+x2)/2 , (y1+y2)/2
=(6+2)/2 ,(6-4)/2
= 8/2 ,2/2
=4, 1
5. D
6.G
7.B
8.J
9.C
10.F
Sorry it took time.
Answer:
B
Step-by-step explanation:
8x^2+x+3 follows the rules of being a polynomial due to the three terms being added to each other, and that they are in descending order.